2016
DOI: 10.3892/ol.2016.4717
|View full text |Cite
|
Sign up to set email alerts
|

Invasive micropapillary component and its clinico-histopathological significance in patients with colorectal cancer

Abstract: Abstract. Micropapillary components are located in distinct, empty spaces resembling lymphatic vessels and consist of clusters of cancer cells that adhere tightly to one another. These structures do not have a fibrovascular core. Invasive micropapillary components (IMPCs) exhibit reverse polarity, which results in a characteristic 'inside-out' structure. The aim of the present study was to examine the histological significance of the micropapillary component in colorectal carcinoma compared with conventional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…At histopathology, MPA is defined by the presence of small, tight, round to oval, cohesive clusters of neoplastic cells floating in clear spaces, lined by delicate strands of fibro-collagenous stroma without endothelial lining and with no evidence of inflammatory cells (Figure 3C). This aspect is probably due to peritumoral tissue retraction and to the reversed polarity of the tumor cell in the clusters (“inside-out” growth pattern) [50,56]. This latter aspect is confirmed by their inverted immunohistochemical MUC1 expression, lack of MUC2 stain and loss or altered pattern of E-cadherin stain.…”
Section: Micropapillary Adenocarcinoma (Mpa)mentioning
confidence: 99%
“…At histopathology, MPA is defined by the presence of small, tight, round to oval, cohesive clusters of neoplastic cells floating in clear spaces, lined by delicate strands of fibro-collagenous stroma without endothelial lining and with no evidence of inflammatory cells (Figure 3C). This aspect is probably due to peritumoral tissue retraction and to the reversed polarity of the tumor cell in the clusters (“inside-out” growth pattern) [50,56]. This latter aspect is confirmed by their inverted immunohistochemical MUC1 expression, lack of MUC2 stain and loss or altered pattern of E-cadherin stain.…”
Section: Micropapillary Adenocarcinoma (Mpa)mentioning
confidence: 99%
“…The proportion of an MPC component needed for the diagnosis of MPC has not yet been decided, whereas special variants of CRC such as mucinous adenocarcinoma or signet ring cell carcinoma are designated such, if more than 50% of the lesion is composed of mucin or signet ring cells. Currently, most studies using micropapillary component involving 2-5% of the tumor volume have demonstrated the aggressive biologic behavior, which is irrespective of the percentage of the MPC component [7, 30]. Therefore, recognition of MPC component is important as MPC appears to be an aggressive variant of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Such micropapillary structure can be seen with many other cancers, often constitutes one of the morphological tumor components and coexists with other histological types of cancer, or rarely it can be the only morphological pattern. Studies have shown that CRCs even with micropapillary component involving 2-5% of the tumor volume demonstrate more aggressive behavior compared to conventional CRCs [6, 7]. However, the mechanisms by which the MCs obtain nutrients and gain aggressive biological behavior in the absence of a fibrovascular core and the formation of cell clusters with surrounding empty spaces are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…PDCs and the micropapillary pattern seen in several colorectal cancers are suspected to share the same biological basis [ 63 ] and occasionally display morphologic similarity. Indeed, although uncommonly seen in approximately 4-13% of colorectal cancers, a micropapillary component may be present over between 5-95% of their surface, located mostly at their invasive front [ 74 , 75 ]. The micropapillary component consists of clusters of cancer cells located within intra- or peritumoral empty spaces resembling (but not being) lymphatic vessels, lack a fibrovascular core and present reverse polarity, resulting in secretory activity in the stroma-facing surface [ 74 ].…”
Section: Pdcsmentioning
confidence: 99%
“…Indeed, although uncommonly seen in approximately 4-13% of colorectal cancers, a micropapillary component may be present over between 5-95% of their surface, located mostly at their invasive front [ 74 , 75 ]. The micropapillary component consists of clusters of cancer cells located within intra- or peritumoral empty spaces resembling (but not being) lymphatic vessels, lack a fibrovascular core and present reverse polarity, resulting in secretory activity in the stroma-facing surface [ 74 ]. When compared to those without, colorectal cancers with a micropapillary component exhibit aggressive biological behavior, as they have greater lymphatic metastatic potential [ 74 , 76 ], a higher risk of being unresectable [ 75 ] and significantly lower survival rates [ 74 ].…”
Section: Pdcsmentioning
confidence: 99%